2016
DOI: 10.3389/fonc.2016.00002
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Care Delivery and Women’s Health: The Role of Patient Navigation

Abstract: BackgroundPatient navigation (PN) is a patient-centered health-care service delivery model that assists individuals, particularly the medically underserved, in overcoming barriers (e.g., personal, logistical, and system) to care across the cancer care continuum. In 2012, the American College of Surgeons Commission on Cancer (CoC) announced that health-care facilities seeking CoC-accreditation must have PN processes in place starting January 1, 2015. The CoC mandate, in light of the recent findings from centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 65 publications
0
66
0
Order By: Relevance
“…Several review articles and large clinical trials have focused on the benefits of patient navigation for cancer screening and diagnostic evaluation following abnormal screening [7][8][9]. Most of these studies have found modest overall benefits of patient navigation in these areas.…”
Section: Patient Navigation In Cancer Screening and Diagnostic Evaluamentioning
confidence: 99%
See 1 more Smart Citation
“…Several review articles and large clinical trials have focused on the benefits of patient navigation for cancer screening and diagnostic evaluation following abnormal screening [7][8][9]. Most of these studies have found modest overall benefits of patient navigation in these areas.…”
Section: Patient Navigation In Cancer Screening and Diagnostic Evaluamentioning
confidence: 99%
“…The current literature on patient navigation in active management of patients with cancer has demonstrated mixed findings on improving timeliness or completion of care, with little data on either quality of care or patient experience with navigation [8,10]. Several studies have shown minimal benefit in the cancer care setting.…”
Section: Patient Navigation In Cancer Carementioning
confidence: 99%
“…Few studies have focused on the last phase of life 5,8 . A number of qualitative 7 and intervention or disease cohort studies, including randomized trials 8 , have been carried out, but we found no population-based studies that identify the individuals who are and are not using navigation.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have focused on the last phase of life 5,8 . A number of qualitative 7 and intervention or disease cohort studies, including randomized trials 8 , have been carried out, but we found no population-based studies that identify the individuals who are and are not using navigation. Furthermore, the need for navigation might be changing, given the accelerating discovery of innovative cancer treatments, the fact that more people are living longer with cancer 9 , the current focus on narrowing the gap between oncology and primary care 10,11 , the aging of the population, and greater interest in advance care planning and a palliative approach to care [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation